2022
DOI: 10.52711/0974-360x.2022.00965
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cinamic acid and Costus roots extract against MDR-K. pneumoniae isolated from patients of COVID-19

Abstract: The emergence of resistant Klebsiella pneumoniae associated with COVID-19 demonstrate a primary challenge for the antimicrobial therapy of infectious diseases and increases the incidence of mortality and morbidity. "K. pneumoniae isolated from COVID-19 patient's sputum with ratio (100%). All K. pneumoniae clinical isolates had 100% resistance to ceftriaxone, piperacillin (80%), cefepime (60%), amikacin (40%), and meropenem =levofloxccin (20%). Bacterial isolates gave positive result for mCIM with ratio was 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Consequently, cinnamic acid shows promise as a safe treatment option for skin wound infections (Mingoia et al, 2022) . A new search study has shown that cinnamic acid effectively hindered the formation of biofilms in K. pneumoniae (Hussein et al, 2022).One suggested mechanism suggests that phenolic compounds may target the peptidoglycan within the bacterial cell wall, thereby influencing their ability to inhibit biofilm formation (Bali et al, 2019). Furthermore, another suggested mechanism potentially inhibits N-acyl homoserine lactones (AHLs)mediated quorum sensing (Zhang et al 2020).…”
Section: Antibiofilm Of Cinnamic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, cinnamic acid shows promise as a safe treatment option for skin wound infections (Mingoia et al, 2022) . A new search study has shown that cinnamic acid effectively hindered the formation of biofilms in K. pneumoniae (Hussein et al, 2022).One suggested mechanism suggests that phenolic compounds may target the peptidoglycan within the bacterial cell wall, thereby influencing their ability to inhibit biofilm formation (Bali et al, 2019). Furthermore, another suggested mechanism potentially inhibits N-acyl homoserine lactones (AHLs)mediated quorum sensing (Zhang et al 2020).…”
Section: Antibiofilm Of Cinnamic Acidmentioning
confidence: 99%
“…Only recently, the significance of biofilm has been developed as a crucial microbial survival strategy, along with its substantial impact on various human activities, been recognized and understood (Claessen et al 2014). The five stages of biofilm formation include i) Attachment, ii) Colonization, iii) Proliferation, iv) Maturation and v) Dispersion (Hussein et al 2022). In light of the increasing antibiotic resistance, there is a pressing need to search for alternative inhibitory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceuticals 2023, 16, x FOR PEER REVIEW 3 and economic feasibility [8,9]. S. virgaurea (SV) consisted of many active compounds lead for using it in the treatment of many diseases, including kidney inflammation, nary tract infection, cystitis, diarrhea and arthritis [10,11].…”
Section: Distribution Of P Aeruginosa According To Sourcementioning
confidence: 99%
“…These sources are particularly appealing due to their minimal toxicity, beneficial pharmacological effects Due to advancements in scientific knowledge regarding the medicinal attributes of plants, there has been a surge of interest in natural sources of antibiotics. These sources are particularly appealing due to their minimal toxicity, beneficial pharmacological effects and economic feasibility [8,9]. S. virgaurea (SV) consisted of many active compounds that lead for using it in the treatment of many diseases, including kidney inflammation, urinary tract infection, cystitis, diarrhea and arthritis [10,11].…”
Section: Introductionmentioning
confidence: 99%